PERKEMBANGAN ANAK MASA USIA DINI 2-6 TAHUN - pardomuan, syahril; radianti, anisyah; dalimunthe, rahmah yasrah; Wahyuni, Sri (Nunchi : Islamic Parenting Journal, 2023)
The results showed that during this period many patterns of behavior and attitudes were formed as well as patterns of emotional expression or known as the golden age. Infancy lasts for the first two years after the newborn period. The golden period of growth and development is a very effective period in maximizing the intelligence potential of every baby to create quality human resources. The stages of human infant development are at the sensorimotor stage. and in infancy the physical development can be observed clearly, at the age of six months the growth and development is rapid. At an early age, all aspects of development during the growth period influence each other. That is, in the absence of one of these aspects, whether physical, emotional, intellectual, social and religious, then all aspects of individual development influence each other. The golden age can provide solutions to the problems of Islamic education by developing Kamil's personality from an early age.